2004
DOI: 10.1021/bi0355140
|View full text |Cite
|
Sign up to set email alerts
|

X-ray and NMR Studies of the DNA Oligomer d(ATATAT):  Hoogsteen Base Pairing in Duplex DNA

Abstract: We present and analyze the structure of the oligonucleotide d(ATATAT) found in two different forms by X-ray crystallography and in solution by NMR. We find that in both crystal lattices the oligonucleotide forms an antiparallel double helical duplex in which base pairing is of the Hoogsteen type. The double helix is apparently very similar to the standard B-form of DNA, with about 10 base pairs per turn. However, the adenines in the duplex are flipped over; as a result, the physicochemical features of both gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
85
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 57 publications
(68 reference statements)
5
85
1
1
Order By: Relevance
“…In particular, the overall shape of the molecule demonstrates a narrow minor groove and the helical axis displaced towards one side of the base pairs, as expected for a Hoogsteen duplex. [1] The coiled coils in the crystal do not show any obvious lateral interactions. It appears that coiling is an intrinsic feature of these oligonucleotides and not due to crystal packing; this explains the strong tendency to screw disorder ( Figure 2).…”
Section: Structure Of the Dna Coiled Coil Formed By D(cgatatatatat)mentioning
confidence: 94%
See 2 more Smart Citations
“…In particular, the overall shape of the molecule demonstrates a narrow minor groove and the helical axis displaced towards one side of the base pairs, as expected for a Hoogsteen duplex. [1] The coiled coils in the crystal do not show any obvious lateral interactions. It appears that coiling is an intrinsic feature of these oligonucleotides and not due to crystal packing; this explains the strong tendency to screw disorder ( Figure 2).…”
Section: Structure Of the Dna Coiled Coil Formed By D(cgatatatatat)mentioning
confidence: 94%
“…Daniela De Luchi, [a] Valentina Tereshko, [b] Catherine Gouyette, [c] and Juan A. Subirana* [a] AT-rich sequences of DNA are highly polymorphic, as we have reviewed elsewhere [1] and are abundant in noncoding regions of the genome. [1,2] As part of our studies on these sequences, we have determined the molecular structure of the coiled coil obtained from duplex d(CGATATATATAT) by single-crystal X-ray diffraction.…”
Section: Structure Of the Dna Coiled Coil Formed By D(cgatatatatat)mentioning
confidence: 99%
See 1 more Smart Citation
“…There are also few structural studies of oligonucleotides with such sequences. Only the alternating fragments d(ATAT) (6) and d(ATATAT) (7,8) have been crystallized. Based on the structure of d(ATAT), an alternating model of DNA was proposed (9).…”
mentioning
confidence: 99%
“…The structural alternation was later confirmed in crystallized oligonucleotides (10), although the details of the structure were different. d(ATATAT), however, crystallizes as a duplex structure with Hoogsteen base pairs (7,8). Fiber diffraction studies have also shown that AT sequences are strongly polymorphic (11).…”
mentioning
confidence: 99%